FENOMENA MIGRASI TENAGA KERJA DAN PERANNYA BAGI PEMBANGUNAN DAERAH ASAL: STUDI EMPIRIS DI KABUPATEN WONOGIRI - Purnomo, Didit (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2009)
This research analyzes (a) patterns of labor migration from Wonogiri Regency, (b) the impact of migration on the welfare level by taking into account the income level of migrant Wonogiri Regency, and (c) the role of migrants seen from homelands conditions. The results of binary logistic analysis showed that the variables age, education, and marital status, have a significant effect on intention nomads to settle in the overseas area. Based on survey findings in the field, 88.8 percent of Wonogiri nomads do not want to settle in the overseas regions. The economic analysis through linear regression analysis to explain the role of the nomads and the impact on the regional origin that shows only one independent variable that is used has a significant influence on the local nomads income overseas, namely: level of education, while the other independent variables are family dependents, ownership of property in the area of origin, length of stay in overseas, and marital status had no significant effect.